PEMBERDAYAAN MASYARAKAT MELALUI USAHA HOME INDUSTRY KERIPIK KACA DI DESA PASANGGRAHAN KECAMATAN KASOMALANG KABUPATEN SUBANG - Ajat Saputra; Afif Nurseha; Dewi Syatia Lestari; Hani Fitriani; Kirey Marladillah (Yayasan Education and Social Center, 2022)
Abstract Home industry is a business unit or company on a small scale that is engaged in certain fields. Glass Chips Business (KIRCA) is one of the businesses that is well known in the Subang City area. Especially Pasanggrahan Village and its surroundings. The Home Industry's role is very meaningful in empowering the community to have independence in the economic field. 18/06 Pasanggrahan Village Kasomalang Subang District, which was the first originator of the famous glass chip business. A good business strategy is needed to deal with increasingly complex and competitive business competitiontacle in facing development and marketing. Until the time of the covid 19 pandemic arrived, it became an obstacle and obs The objectives of this research are (1) To determine the effect of internal environmental conditions and external environmental conditions on the development of businesses made from cassava. (2) To find out the improvement of the community's economy, (3) To find out what needs to be considered to make and process cassava cassava into glass chips during the current pandemic. The research method used in the research is qualitative analysis. And an effort to overcome this problem is to find new innovations in its manufacture and marketing strategies through appropriate informations technology. This research was conducted in Pasanggarahan Village, Kasomalang District, Subang Regency. The data collection technique in this study was conducted by interview and then analyzed by SWOT. The sampling method was random sampling. The type of data consists of secondary primary data. Aggressive empowerment application means that the glass chip business is in a very profitable situation or has the opportunity and strength.